The best snacks for kids: the importance of beavers Castor fiber in the diet of wolf Canis lupus pups in north-western Poland. Issue 6 (2nd November 2019) - Mysłajek, Robert W.; Tomczak, Patrycja; Tołkacz, Katarzyna; Tracz, Maciej; Tracz, Magdalena; Nowak, Sabina
Abstract : We assessed the diet of adult wolves and their pups in an area recently recolonized by the species in north-western Poland, through the analysis of scats. Adult wolves preyed mostly on wild ungulates (94.8% of food biomass), with roe deer (45.0%) and red deer (37.8%) being the most important food sources, and occasionally on beavers (5.6%). Pups ate less ungulates (76.3%), but many more beavers (19.8%). Our study documented the importance of beavers as a food source for wolf pups in regions recolonized by the species in Central Europe, and highlighted the necessity for studies on ontogenetic changes in the wolf diet.